MAJORITY ACQUISITIONS VS MINORITY ACQUISITIONS: A PRE- AND POST ACQUISITION FINANCIAL ANALYSIS OF INDIAN PHARMACEUTICAL COMPANIES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The purpose of the study is to analyze the  financial performance of Indian Pharmaceutical  Acquirers and compare the pre- and post financial performance of acquirers conducting  minority and majority acquisitions. The  financial analysis was conducted on the data  of 13 acquisition deals for the period between  2010 and 2019 by comparing the three-year  pre- and post-acquisition periods until the  year 2023 using the paired t-test methodology.  The findings of the study revealed that there  is no significant difference in the profitability  and liquidity positions of the acquirers in the  pre- and post-acquisition periods. Finally, the  comparison between the financial performance  of majority and minority acquisitions shows  that the financial performance of acquirers  deteriorates after the post-acquisition period,  but the performance of majority acquisitions’  acquirers is still better when compared to  minority acquisitions.
Keywords: Minority acquisitions; majority acquisitions; India; paired t-test; financial performance; pharmaceutical industry